PENGARUH VIDEO EDUKATIF “AKU SIAP, AKU SELAMAT” TERHADAP PENINGKATAN PEMAHAMAN MITIGASI BENCANA BAGI SISWA TUNAGRAHITA DI SLB - Yuniar, Nisa; Idhartono, Amelia Rizky; Jauhari, Muhammad Nurrohman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the low understanding of students with intellectual disabilities at Batu State Special Needs School regarding the risks and mitigation of natural disasters, even though they are located in a geographical area prone to flash floods. This lack of knowledge creates a serious safety threat due to unpreparedness for emergency situations. The focus of this study is to evaluate the effect of the educational video entitled